2012
DOI: 10.1002/hep.25564
|View full text |Cite
|
Sign up to set email alerts
|

Zinc finger transcription factor 191, directly binding to β-catenin promoter, promotes cell proliferation of hepatocellular carcinoma

Abstract: Activation of b-catenin, the central effector of the canonical wingless-type (Wnt) pathway, has been implicated in hepatocellular carcinoma (HCC). However, the transcription regulation mechanism of the b-catenin gene in HCC remains unknown. Here we report that human zinc finger protein 191 (ZNF191) is a potential regulator of b-catenin transcription. ZNF191, a Krüppel-like protein, specifically interacts with the TCAT motif, which constitutes the HUMTH01 microsatellite in the tyrosine hydroxylase (TH) gene ex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
63
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(72 citation statements)
references
References 69 publications
9
63
0
Order By: Relevance
“…Promoter luciferase assay indicated that the wild-type ZNF24 can increase transcription activity of CTNNB1 promoter by about 2.7 fold compared with transfecting control vector (Figure 7). This is consistent with previous reports that ZNF24 can activate β-Catenin in hepatocellular carcinoma cell lines[9]. In contrast, when the ZF region was missing, the ZNF24 mutants failed to activate the CTNNB1 promoter (Figure 7, compare dZF1-2 or p1-250 with WT).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Promoter luciferase assay indicated that the wild-type ZNF24 can increase transcription activity of CTNNB1 promoter by about 2.7 fold compared with transfecting control vector (Figure 7). This is consistent with previous reports that ZNF24 can activate β-Catenin in hepatocellular carcinoma cell lines[9]. In contrast, when the ZF region was missing, the ZNF24 mutants failed to activate the CTNNB1 promoter (Figure 7, compare dZF1-2 or p1-250 with WT).…”
Section: Discussionsupporting
confidence: 92%
“…Allelic variations of HUMTH01 are known to have a quantitative silencing effect on TH gene expression and to correlate with quantitative and qualitative changes in the binding by ZNF24[8]. ZNF24 also can directly bind to CTNNB1 promoter, and activates the expression of β-Catenin and promotes cell proliferation of hepatocellular carcinoma[9]. ZNF24 shows 94% identity to its mouse homologue Zfp191, which is the most highly conserved among the human-mouse SCAN family member orthologues pairs[10].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, only a few previous studies have provided evidence for a transcriptional mechanism of β -catenin regulation. 24, 25 Here our study provides solid evidence for a transcriptional mechanism of β -catenin regulation in CRC carcinogenesis. The ChIP, EMSA and luciferase assays revealed that Elf3 could bind to the promoter of β -catenin and transactivate its transcription.…”
Section: Discussionmentioning
confidence: 55%
“…ZNF 191 may activate the expression of β-catenin and its downstream target genes (Liu et al, 2012). β-catenin has been implicated in depression (Dias et al, 2014), glucose metabolism (Elghazi et al, 2012), and idiopathic pulmonary fibrosis (Chilosi et al, 2003).…”
Section: Discussionmentioning
confidence: 99%